2012
DOI: 10.1371/journal.pone.0039394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Ivabradine versus Carvedilol in Murine Model with the Coxsackievirus B3-Induced Viral Myocarditis

Abstract: BackgroundElevated heart rate is associated with increased cardiovascular morbidity. The selective If current inhibitor ivabradine reduces heart rate without affecting cardiac contractility, and has been shown to be cardioprotective in the failing heart. Ivabradine also exerts some of its beneficial effects by decreasing cardiac proinflammatory cytokines and inhibiting peroxidants and collagen accumulation in atherosclerosis or congestive heart failure. However, the effects of ivabradine in the setting of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…This finding was supported by Kleinbongard et al who observed in a mouse model that ivabradine reduces infarct size in the absence of heart rate reduction [16]. Additionally, ivabradine was demonstrated to inhibit the production of proinflammatory cytokines such as IL-6 and TNF-alpha, as well as the chemokine MCP-1 [9]. In myocarditis, treatment with ivabradine led to inhibition of myocardial fibrosis, prevention of LV-EF worsening, and improvement of survival [9].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…This finding was supported by Kleinbongard et al who observed in a mouse model that ivabradine reduces infarct size in the absence of heart rate reduction [16]. Additionally, ivabradine was demonstrated to inhibit the production of proinflammatory cytokines such as IL-6 and TNF-alpha, as well as the chemokine MCP-1 [9]. In myocarditis, treatment with ivabradine led to inhibition of myocardial fibrosis, prevention of LV-EF worsening, and improvement of survival [9].…”
Section: Introductionmentioning
confidence: 67%
“…Heart rate reduction results in improved myocardial oxygen supply via a prolonged diastolic filling time, as well as improved ventricular filling. In patients with CHF, ivabradine has a beneficial effect on left ventricular remodeling [9] and survival [10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported improvement in right ventricular function with ivabradine might be clinically significant in ChD HF because right ventricular dysfunction is a challenge in the management of ChD HF 18. Concerning the myocarditis, beneficial pleiotropic effects of ivabradine beyond HR were reported in experimental coxsackievirus B3 myocarditis partially mediated by the inhibition of both the production of proinflammatory cytokines and the synthesis of NO by iNOS 19, 20. Also, ivabradine in chronic viral myocarditis in mice significantly increased the survival rate; attenuated the myocardial lesions and fibrosis; improved the impairment of the LV function; diminished the heart dimension; decreased the production of collagen I and collagen III; reduced the expression of the proinflammatory cytokines tumour necrosis factor alpha and interleukins 1β and 6; and lowered the production of phospho‐p38 MAPK 21.…”
Section: Discussionmentioning
confidence: 99%
“…by guest on May 7, 2018 http://hyper.ahajournals.org/ Downloaded from cardiac apoptosis and LV hypertrophy, 35,36 or changes in cardiac protein expression. 37 Such acute mechanical effect of ivabradine is in agreement with previous findings, showing that acute HR reduction has a favorable effect on the depressed wall thickening and increased postsystolic wall thickening during postischemic myocardial stunning.…”
Section: Discussionmentioning
confidence: 99%